A revision of the genus Tambana Moore, 1882 with description of eight new species and one subspecies (Lepidoptera, Noctuidae: Pantheinae). Revision of Pantheinae, contribution XIII - Behounek, G.; Han, H. L.; Kononenko, V. S. (Zootaxa, 2015)
The oriental Pantheinae genus Tambana Moore, 1882 (type-species Tambana variegata Moore, 1882) with 16 previously described species is revised. Eight new species and one subspecies (T. tibetica sp. n., T. xilinga sp. n., T. mekonga sp. n., T. helmuti sp. n., T. fansipana sp. n., T. laura sp. n., T. indeterminata sp. n., T. annamica sp. n., T. annamica stumpfi ssp. n.) are described from China, Vietnam and Myanmar. One unrecognized taxon is included to the revision. Three new synonyms and one new combination are introduced (Trisuloides klapperichii Mell 1958, syn. n. of Tambana entoxantha (Hampson, 1894); Tambana behouneki Speidel & Kononenko, 1998, syn. n. of Tambana glauca (Hampson, 1898); Trichosea gerryi Thöny, 1996, syn. n. of Tambana funebris (Berio, 1973), comb. n. (Trichosea). The updated checklist of 26 taxa of Tambana is presented. Short diagnoses are given for the described species. In addition the related genus Xanthomantis Warren, 1909 with two species X. cornelia (Staudinger, 1888) and X. contaminata (Draudt, 1937) is reviewed.